(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Emotional intelligence is considered instrumental in personal and professional success. Research suggests that EI positively impacts job satisfaction, well-being, and overall performance. This study provides insight into how individuals ranking high on EI are likely to possess high engagement levels. In the competitive business scenario, employees face several challenges due to long working hours, stress, exhaustion, burnout, and a high customer-employee interface to name a few. These conditions adversely impact the engagement levels of employees. In such a scenario, an emotionally intelligent employee will be able to display positive emotions which can propel employee engagement. In this paper, the author attempts to identify potential mediators and moderators between EI and EE that potentially condition this relationship.